Severity of clinical presentation in youth with type 1 diabetes is associated with differences in brain structure. Issue 8 (2nd August 2016) - Siller, Alejandro F.; Lugar, Heather; Rutlin, Jerrel; Koller, Jonathan M.; Semenkovich, Katherine; White, Neil H.; Arbelaez, Ana Maria; Shimony, Joshua; Hershey, Tamara
Abstract : Objective: Differences in cognition and brain structure have been found in youth with type 1 diabetes compared with controls, even after relatively short disease duration. To determine whether severity of clinical presentation contributes to these differences, we obtained structural magnetic resonance imaging (MRI) scans in youth ages 7–17 who were either newly diagnosed with type 1 diabetes (<3.5 months from diagnosis, n = 46) or a sibling without diabetes ( n = 28). Research design and methods: Severity of presentation was measured by the presence of diabetic ketoacidosis (DKA) and degree of hyperglycemia exposure [hemoglobin A1c (HbA1c)] at diagnosis. MRI were obtained using T1‐weighted, T2‐weighted, and diffusion‐weighted sequences. Results: Within the group with type 1 diabetes, 12 subjects presented in DKA and 34 did not. After controlling for age, sex, and multiple comparisons, the type 1 diabetes group had lower volume in the left temporal–parietal–occipital cortex compared with controls. Within the type 1 diabetes group, DKA at presentation was associated with lower radial, axial, and mean diffusivity (MD) throughout major white matter tracts and higher HbA1c was associated with lower hippocampal, thalamic, and cerebellar white matter volumes, lower right posterior parietal cortical thickness, and greater right occipital cortical thickness. Conclusion: These data suggest that severity of clinical presentation is an important factor in predicting brain structural differences in youth with type 1 diabetes approximately 3 months after diagnosis.